Chapter Five Chlamydia A Disease without a History - Worboys, Michael (University of Rochester Press, 2019)
Since the late 1990s chlamydia has been the most commonly reported sexually transmitted infection (STI) in Europe and the United States. The infection is caused by the bacterium Chlamydia trachomatis (C. trachomatis), and its common name follows a pattern established in the late nineteenth century, where an infection is named after its causal pathogen.